2019
DOI: 10.35479/ijretina.2019.vol002.iss001.58
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Silicon Oil Evacuation Procedure In Cipto Mangunkusumo Hospital Indonesia

Abstract: Background: Injection of Silicon oil (SO) is a standard procedure for vitreous replacement in vitrectomy procedure for retinal detachment cases. It acts as a great tamponading agent for reattachment of retinal breaks or retinal detachment. Despite its minor side effect, SO could cause several complications such as cataract, endothelial decompensation, increased intraocular pressure, and secondary glaucoma. Thus needed to be evacuated after the retinal reattachment is stabilized. Following the evacuation proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…A meta-analysis study byHe, et al (2018) states that the condition of PVR before vitrectomy surgery and OS implantation is not a risk of redetached, but the formation of PVR after evacuation of SO can be the main cause of redetached retina. This is in line with this study which found the condition of redetached retina, but indeed the researchers did not assess the degree of PVR in this study 5,17. CONCLUSIONThe research subjects in this study had an age with a median of 51 years with the majority of subjects being in the age range of 46-65 years, female and living in Bali with the majority of phakic and pseudophakic lens status.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…A meta-analysis study byHe, et al (2018) states that the condition of PVR before vitrectomy surgery and OS implantation is not a risk of redetached, but the formation of PVR after evacuation of SO can be the main cause of redetached retina. This is in line with this study which found the condition of redetached retina, but indeed the researchers did not assess the degree of PVR in this study 5,17. CONCLUSIONThe research subjects in this study had an age with a median of 51 years with the majority of subjects being in the age range of 46-65 years, female and living in Bali with the majority of phakic and pseudophakic lens status.…”
supporting
confidence: 69%
“…Second, the mechanical impact of the balanced salt solution (BSS) during the SO evacuation action can divide the SO droplet into smaller droplets, which are more likely to obstruct the trabecular meshwork. 5,12,13,14 The indications for evacuation of SO may vary in each case. In this study, for the most indications, retina reattached > 3 months was 73.9%, while…”
Section: Resultsmentioning
confidence: 99%